Case of patient with extramammary Paget’s disease - A. Z. Tsitskarava; A. N. Demin; A. Yu. Korolkov; S. M. Lazarev (Вестник хирургии имени И.И. Грекова, 2021)
Extramammary Paget’s disease is the infrequently diagnosis in surgical practice, representing a diagnostic challenge. The timely verified diagnosis guarantees successful treatment. We report about a clinical case of the patient with extramammary Paget’s disease of perianal area.